44.5k views
4 votes
3) x2+ y2 - x + 3y - 42 = 0
X+y=4

User Vchuravy
by
5.5k points

1 Answer

5 votes

The solution is
(-1,5) and
(7,-3)

Explanation:

The expression is
x^(2) +y^(2) -x+3y-42=0 and
x+y=4

Using substitution method we can solve the expression.

Let us substitute
x=4-y in
x^(2) +y^(2) -x+3y-42=0


(4-y)^(2) +y^(2) -(4-y)+3y-42=0

Expanding and simplifying the expression, we get,


\begin{array}{r}{16-8 y+y^(2)+y^(2)-4+y+3 y-42=0} \\{2 y^(2)-4 y-30=0}\end{array}

Let us use the quadratic equation formula to solve this equation,


\begin{aligned}y &=(4 \pm √(16-4(2)(-30)))/(2(2)) \\&=(4 \pm √(16+240))/(4) \\&=(4 \pm 16)/(4) \\y &=1 \pm 4\end{aligned}

Thus,
y=5 and
y=-3

Substituting y-values in the equation
x+y=4, we get the value of x.

For
y=5
x=4-5=-1

For
y=-3
x=4+3=7

Thus, the solution set is
(-1,5) and
(7,-3)

User Mark Gibaud
by
4.9k points